Research on the influence mechanism of privacy invasion experiences with privacy protection intentions in social media contexts: Regulatory focus as the moderator - Chen, Subai; Gu, Chenyu; Wei, Juan; Lv, Mingjie (Frontiers in Psychology, 2023)
In recent years, there have been numerous online privacy violation incidents caused by the leakage of personal information of social media users, yet there seems to be a tendency for users to burn out when it comes to privacy protection, which leads to more privacy invasions and forms a vicious circle. Few studies have examined the impact of social media users' privacy invasion experiences on their privacy protection intention. Protection motivation theory has often been applied to privacy protection researches. However, it has been suggested that the theory could be improved by introducing individual emotional factors, and empirical research in this area is lacking. To fill these gaps, current study constructs a moderated chain mediation model based on protection motivation theory and regulatory focus theory, and introduces privacy fatigue as an emotional variable. An analysis of a sample of 4800 from China finds that: 1, social media users' previous privacy invasion experiences can increase their privacy protection intention, this process mediated by response costs and privacy fatigue. 2, Privacy fatigue plays a masking effect, i.e., in-creased privacy invasion experiences and response costs increase individuals' privacy fatigue, and the feeling of privacy fatigue significantly reduces individuals' willingness to protect their privacy. 3, Promotion-focus individuals are less likely to experience privacy fatigue than those with prevention-focus. In summary, this trend of " lie flat" of social media users' privacy protection is caused by the key factor of "privacy fatigue", and the psychological trait of regulatory focus can be used to interfere with the development of privacy fatigue. This study extends the scope of research on privacy protection and regulatory focus, refines the theory of protection motivation, and expands the empirical study of privacy fatigue; the findings also inform the practical governance of social network privacy.